2013
DOI: 10.1101/gr.161315.113
|View full text |Cite
|
Sign up to set email alerts
|

Functional transcriptomics in the post-ENCODE era

Abstract: The last decade has seen tremendous effort committed to the annotation of the human genome sequence, most notably perhaps in the form of the ENCODE project. One of the major findings of ENCODE, and other genome analysis projects, is that the human transcriptome is far larger and more complex than previously thought. This complexity manifests, for example, as alternative splicing within protein-coding genes, as well as in the discovery of thousands of long noncoding RNAs. It is also possible that significant nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 159 publications
(189 reference statements)
0
64
0
2
Order By: Relevance
“…14,57 Several previous studies have demonstrated an excess of significant GWAS associations in regulatory categories. 5,6,11,58 In particular, Ernst et al 59 observed 23 enrichment in cell-type-relevant enhancers, Schaub et al 8 identified 1.123 enrichment at DHSs, and Maurano et al 3 identified 1.43À1.83 enrichment at DHSs (relative to noncoding SNPs) and enrichment at cell-type-relevant DHSs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…14,57 Several previous studies have demonstrated an excess of significant GWAS associations in regulatory categories. 5,6,11,58 In particular, Ernst et al 59 observed 23 enrichment in cell-type-relevant enhancers, Schaub et al 8 identified 1.123 enrichment at DHSs, and Maurano et al 3 identified 1.43À1.83 enrichment at DHSs (relative to noncoding SNPs) and enrichment at cell-type-relevant DHSs.…”
Section: Discussionmentioning
confidence: 97%
“…13 Although relative enrichment has been documented, the question of how much each category contributes to disease heritability remains unanswered. 14,15 Recently, investigators have used variance-component methods to estimate the total additive variance explained by all genotyped SNPs (h 2 g ), 16,17 and to estimate the h 2 g of many quantitative and dichotomous traits. [18][19][20][21][22] We propose joint estimation of h 2 g from functional-category-specific variance components for assessing enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…With all this overabundance, there is a debate raging between those that claim almost any identified transcript and snippet of RNA to be functional (Mattick 2003;Lee et al 2009;Carninci 2010;Kishore et al 2010;Clark et al 2011;Bernstein et al 2012;Kapranov and St Laurent 2012;Khayrullina et al 2012;Gebetsberger and Polacek 2013;Mattick and Dinger 2013) and more conservative voices (Brosius 2005c;Huttenhofer et al 2005;Robinson 2010;van Bakel et al 2010;Graur et al 2013). The writer concurs with the argumentation for spurious and stochastic transcripts (Kowalczyk et al 2012;Jensen et al 2013;Mudge et al 2013), especially as many transcription promoters are bidirectional (Seila et al 2008;Neil et al 2009;Xu et al 2009;Wei et al 2011;Uesaka et al 2014). Even the yeast Saccharomyces cerevisiae featuring a compact genome abounds with transcriptional noise and erroneous initiation of transcription by RNA polymerase II (Struhl 2007).…”
Section: Did Rna Enter Bubble Territory?mentioning
confidence: 90%
“…Therefore they were very difficult to be discovered by both methods [49]. We have detected 62 novel proteins missing in Refseq.…”
Section: Discussionmentioning
confidence: 98%
“…http://dx.doi.org/10.1101/012112 doi: bioRxiv preprint first posted online Dec. 4, 2014; evolution [49]. We provided hundreds of such "young" transcripts.…”
Section: Exploring Novel Genesmentioning
confidence: 99%